IMPLEMENTASI LITERASI DIGITAL DI KALANGAN MAHASISWA - Agus Syabaruddin; Imamudin Imamudin (Universitas Labuhanbatu, 2022)
The rapid development of technology has made social media a place to share many things and information, of course not only positive things but also negative things so that all users need to be wise in using them. As it is well known that students oftenÂ have the task of writing articles that require relevant reference sources, there are not a few students who copy and paste their assignments. This is one of the impacts of not applying digital literacy. This research article uses the literature study method in which data collection is done by reading, taking notes and analyzing. All social media users, including users who dominate social media, namely the younger generation or students have an important role in implementing digital literacy in everyday life. This article discusses how to implement digital literacy for students starting from the constraints of student digital literacy in Indonesia, the reality of digital literacy among students in Indonesia and things that need to be developed to improve digital literacy among students with the aim that students better understand the need to be smart in use social media.Keywords: Student digital literacy; digital literacy for student; digital literacy skills for student